Assimilation Processes Among Immigrants: A Study of German and Italian Immigrants to Hamilton - Fenton, Stephen Charles (My University, 1968)
This study is concerned with the processes of assimilation among immigrants and focusses on primary relation, life-style, and identification. The introduction and chapter one set the context of the study and review the literature. Chapter two deals with a number of hypotheses, chapter three describes the methodology. In chapter four the data are presented and discussed.
Keywords: Sociology; Sociology